The Experiences of Learning Engagement by Successful Pre-service Teachers during Teaching Internship Program - Al Mubarokah, Laelah; Pradita, Intan (Journal of English and Education (JEE), 2022)
Pre-service teachers’ (PST) learning engagement in online learning as the contributing factor in determining students’ successful learning was less elaborated. It is important to explore the process of having meaningful learning engagement experiences. This study aims at elaborating on how learning engagement and meaning making, as experienced by two pre-service teachers, inspired them to successfully teach online in a variety of student contexts with the tools provided. The participants of this study were two pre-service teachers who participated in teaching internships as a mandatory program from their university. The type of this study was qualitative and was then analyzed by narrative analysis. Through multiple interviews and three months of Instagram stories, this study found two pre-service teachers employed learning engagement, especially cognitive engagement, in their distance learning process. The finding was elaborated into two themes; (1) cognitive engagement as a meaningful experience and (2) shared responsibility to achieve behavioral engagement.